An unexpected diversity of powdery mildew species infecting the Fabaceae in Australia - Lisa A. Kelly; Buddhika A. Dahanayaka; Niloofar Vaghefi; Aftab Ahmad; Levente Kiss (PLoS ONE, 2025)
The Fabaceae family has been reported to host more than fifty species of powdery mildew worldwide. Despite being commonly found on fabaceous hosts throughout Australia, the accurate identification of many powdery mildew species remains uncertain. The objective of this study was to identify powdery mildew species that naturally occur on fabaceous hosts in Australia and provide insight into those native and weedy species that may host crop pathogens and contribute to disease in cropping systems. The ribosomal DNA internal transcribed spacer (ITS) sequences and morphology of 34 fresh and 40 herbarium powdery mildew specimens infecting diverse Fabaceae species in Australia were characterised in this study. Altogether, a total of eleven powdery mildew species were identified from 51 Fabaceae species. Podosphaera xanthii was the most common powdery mildew in this study and was detected on 18 host species across ten genera. Ten species of Erysiphe were confirmed on 37 host species covering 17 host genera, with E. diffusa and E. cf. trifoliorum the most prevalent. This work provides the most comprehensive catalogue of powdery mildew species infecting legume hosts throughout Australia.